Financial hegemony and the unachieved European state. (April 2015) - Durand, Cédric; Keucheyan, Razmig
This article addresses a classic problem in the social sciences: what allows for or, on the contrary, prevents, the emergence of democratic institutions, i.e., of modern democratic statehood. This problem is tackled in relation to the internal socio-political logic of the European integration process. Drawing on the political economy of the French Regulation School and Poulantzas's approach to the modern democratic state, the authors argue that the absence of state-like, democratic institutions at the EU level is the outcome of a cumulative process of exclusion of labour and a monopolization of the agenda by transnational and financial capital, preventing the institutional crystallization of conflicting European class relations.